Design of IIOT Device Based on LoRa for Parsing Data Directly to SCADA System - Rini Puji Astutik; Julmy Lesmana Putra; Rahmad Maulana (Advance Sustainable Science Engineering and Technology, 2024)
As the revolution industry 4.0 was started as well as the productivity increases, the need for data analysis increases. Some industries have wide production area and they need long wire to connected between office for transferring data. A wireless system is one of solution to overcome this issue so that the technique of parsing data to expand coverage area for both local and remote systems. In this research, a device that supports IIOT (Industry on Internet of Things) will be designed by utilizing LoRa technology connected to a SCADA (Supervisory Control and Data Acquisition) system for direct parsing data. By using a SCADA system concept and incorporating wireless system as well as connecting to internet so the industrial system can be monitoring from anywhere so productivity can be increased. To test the proposed design, the two scenarios of performance test have been done, they are communicating distance test and the parsing data between two nodes LoRa as well as connecting to SCADA system. The first scenario results in the maximum communication distance that can still carried out reaching 400m. Meanwhile, the experience of second scenario on the IIOT device prototype produces accurate data so that it can be implemented in the wider industry